Budget Efficiency Policy In the Perspective of Sharia Economic Law - Ulfa Jamilatul Farida (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study is to respond to government budget efficiency as an effort to restore the budget as a vital instrument in the country's economy. Efficiency in budget management can have a significant impact on various aspects of the economy. In accordance with the Presidential Instruction of the Republic of Indonesia Number 1 Year 2025, there are budget cuts to several activities. Budget cuts certainly need to be supported by considering the right analysis and measuring the implications of these actions. Based on the above background, this paper has a problem question: “How is the Budget Efficiency Policy in the perspective of Sharia Economic Law?” This research uses a qualitative and analytical approach. By using the concept of budget efficiency, sharia economic law in the context of maqashid sharia, this research produces the following conclusions: First, the budget efficiency policy aims to ensure that state spending is used as efficiently as possible, with a focus on the welfare of the people and this is in accordance with maqashid sharia in the economic field, namely al-falah. Second, budget efficiency as a government policy is in accordance with the objectives of sharia economics as long as the process is ideally in accordance with the legal principles of sharia economics.